2023
DOI: 10.2106/jbjs.oa.22.00084
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Orthopaedic Surgery Residency Interviews

Abstract: Background: Interviews are a critical component of orthopaedic surgery residency selection for both the applicant and the program. Some institutions no longer report Alpha Omega Alpha (AOA) designation or class rank, and US Medical Licensing Examination (USMLE) Step 1 recently switched to pass/fail scoring. During the coronavirus disease 2019 (COVID-19) pandemic, all Accreditation Council for Graduate Medical Education programs conducted virtual interviews and subinternship rotations were restricted. These cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Non-Hispanic Whites made up 82.9%, Asian American and Pacific Islanders made up 6.7%, Black or African Americans made up 5.7%, and Hispanic or Latino made up 1.9% of residency program directors in orthopaedic surgery. 8 The lack of diversity in orthopaedic surgery is not only limited to residency programs, but fellowships in orthopaedic surgery also face the same issue. In 2023, The Journal of Arthroplasty reported that during the 14-year time frame between 2007-2021, men trainees remained high with an overall average percentage of 88% and demonstrated increasing representation (p=0.012).…”
Section: Resultsmentioning
confidence: 99%
“…Non-Hispanic Whites made up 82.9%, Asian American and Pacific Islanders made up 6.7%, Black or African Americans made up 5.7%, and Hispanic or Latino made up 1.9% of residency program directors in orthopaedic surgery. 8 The lack of diversity in orthopaedic surgery is not only limited to residency programs, but fellowships in orthopaedic surgery also face the same issue. In 2023, The Journal of Arthroplasty reported that during the 14-year time frame between 2007-2021, men trainees remained high with an overall average percentage of 88% and demonstrated increasing representation (p=0.012).…”
Section: Resultsmentioning
confidence: 99%
“…In the 2022 National Residency Match Program (NRMP) survey of program directors, 63% of respondents reported that they seldom or never interview osteopathic applicants while only 16% reported that they seldom or never interview allopathic applicants 8 . This lack of diversity and osteopathic representation is seen throughout the academic spectrum including residents, program directors, and even literature publication rates for orthopaedic journals 9-12 .…”
Section: Introductionmentioning
confidence: 99%
“…According to National Resident Matching Program data, the average orthopaedic surgery match rate is around 70% over the past 8 years [1][2][3][4][5][6][7][8] . Factors such as research productivity, USMLE scores, volunteer and leadership activities, AOA membership, and medical school rank have all been associated with increased likelihood to match [9][10][11][12][13][14][15][16][17][18][19][20][21] . However, there is limited evidence that these factors predict successful performance during residency 16,22,23 .…”
Section: Introductionmentioning
confidence: 99%